An Introduction to Mechanical Engineering, Enhanced Edition, 4th Edition - Jonathan Wickert; Kemper Lewis (Cengage Learning, 2020)
Introduce your students to the latest developments in today's ever-changing field of mechanical engineering with Wickert/Lewis' ENHANCED EDITION OF AN INTRODUCTION TO MECHANICAL ENGINEERING, 4th Edition. This engaging approach demonstrates how engineers design hardware that builds and improves societies around the world. Students in their first two years of a mechanical engineering program or a closely related field can benefit as this edition emphasizes technical problem-solving skills with a balance of design, engineering analysis, and modern technology. The authors present engineering as an exciting visual and graphical activity as this edition highlights real-world applications and interesting examples using approximately 300 engaging photographs and illustrations.